2011
DOI: 10.1002/wmon.2
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of fire and nonnative plants on small mammals in Grasslands

Abstract: Contrast in vegetation composition and structure between 2 nearby areas of semi-desert grassland, 1 dominated by native grasses (top) and 1 dominated by a nonnative grass, Eragrostis lehmanniana (bottom). Photo by our friend and colleague, Eric Albrecht, who studied songbirds on these grasslands as part of his M.S. degree, and who died in 2004.ABSTRACT Invasions by nonnative plants have changed the structure of many terrestrial ecosystems and altered important ecological processes such as fire, the dominant dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 108 publications
(170 reference statements)
2
40
1
2
Order By: Relevance
“…Extensive pre‐fire monitoring data of both small mammal and L. constancei populations could allow the fire to be used as a natural experiment with the potential to find a causal relationship between the two. The specific effects of fire on L. constancei population demographics are particularly difficult to predict, given the potential for interacting effects of fire and small mammal abundance and consumer pressure (Zwolak ; Litt & Steidl ). For example, Zwolak et al .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive pre‐fire monitoring data of both small mammal and L. constancei populations could allow the fire to be used as a natural experiment with the potential to find a causal relationship between the two. The specific effects of fire on L. constancei population demographics are particularly difficult to predict, given the potential for interacting effects of fire and small mammal abundance and consumer pressure (Zwolak ; Litt & Steidl ). For example, Zwolak et al .…”
Section: Discussionmentioning
confidence: 99%
“…Homogenous habitats dominated by nonnative plants can lead to decreased diversity of small mammals (Bartel et al 2008;Litt and Steidl 2011). Arjo et al (2007) and Kozlowski et al (2012) found increased rodent abundances at Dugway, but noted that overall species diversity was low, and that the increase in abundance was likely due to an influx of habitat generalists.…”
Section: R a F Tmentioning
confidence: 99%
“…This is even more complicated because of the problem of scale. For instance, Litt & Steidl (2011) studied "communities" of rodents in 1-ha plots, but who considers one ha to be the extent of interspecific associations?…”
Section: Populationmentioning
confidence: 99%
“…paper studied mule deer in the State of Idaho (Hurley et al 2011), one studied red-cockaded woodpeckers on military land in the USA (Delaney et al 2011), and one studied small mammals on 54 experimentally manipulated 1-ha plots (Litt & Steidl 2011). The "populations" were defined by political boundaries, the research subject, or the sampling units, and this is typical of almost all population ecology.…”
Section: Populationmentioning
confidence: 99%